Screening Blood Glucose Levels at Adolescents in Rongtengah Village, Sampang District - Baterun Kunsah; Nur Vita Purwaningsih; Tanti Puspitasari (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective: Blood glucose is the level of glucose in the blood whose concentration is strictly regulated by the body. Increased blood glucose in adolescents is caused by changes in lifestyle and diet that tend to refer to an unhealthy lifestyle and diet due to frequent consumption of sugary drinks, instant food, or fast food. If this habit cannot be changed, it can lead to blood glucose disease. The purpose of this study was to determine blood glucose levels in adolescents aged 17-20 years in RW 06, Rongtengah, Sampang. Method: The type of research used is descriptive. The population in this study were adolescents aged 17-20 years in Rongtengah Village, Sampang. The research sample was adolescents aged 17-20 years in RT 01 to RT 05, RW 06, a total of 42 people from Rongtengah Village, Sampang. This study used a purposive sampling technique that met the criteria of 17-20 years of age—the technique of checking blood glucose levels using the POCT method with units of mg/dL. Data analysis in this study will be tabulated in tabular form. Result: The results of the study obtained as many as 5 high yield samples, the results of normal blood glucose levels as many as 37 samples. Conclusion: The conclusion of this study shows that adolescents still have the potential to have high blood glucose levels.